IMPLEMENTASI PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI (PNPM) PERDESAAN DI KECAMATAN TOBELO KABUPATEN HALMAHERA UTARA - TUANDALI, MARSENI; RARES, JOICE; LALOMA, ALDEN (Sam Ratulangi University, 2015)
ABSTRAKPNPM Mandiri community empowerment is a national program for povertyreduction as well independence society to grow and evolve in the direction.PNPMprogram can hape petrified society out of the problem of disability and poverty.Then in need of local government’s readiness to accept and implement thePNPM be continue actually be felt by society. Purpose of this study in accordance withthe formulation of the problem is to dentermine how the implementation of comonityemporwerment program (PNPM) contriside in improving socie-ecomonic conditions offamilies in tobelo northern halmahera district.The research method uses destriptive reseacth/destribe and methodskualitatif.informan this study as many as 14 people in charge who know and accept theimpact of the implementation of programsof PNPM tobelo. Data use is the primary dataand data collection methods sekunder with interviews while research is researchintrumen it selt. For data analysis done with together with data colletion, the datainterpresti concluded later in the analysis,a description of the national program selfemprowerment(PNPM) rusal counties in the district tobelo halmahera utara.2Showcased in conclusion that the procces implementatin of PNPM mandiri in thedistrict tobelo in 3 of 6 villages that can be said has been running, althogh there arestill many who have not felt the impact of the program goverment can fix mistakes for abetter direction, so that the need of peaple could be served for the better.